2017
DOI: 10.1002/cae.21801
|View full text |Cite
|
Sign up to set email alerts
|

VGLS: A virtual geophysical laboratory system based on C# and viustools and its application for geophysical education

Abstract: It is not hard to find that the forms of traditional education have limitations. The Virtual Laboratory is to provide a virtual experimental environment to the users via computers in controlling engineering by resorting to the virtual reality technology. It was famous for helping students study the complex process of experiments as well as saving time and cost. Therefore, in the new century, it has become more popular as a means of education. In this paper, we present a virtual geophysical laboratory system (V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 22 publications
0
10
0
1
Order By: Relevance
“…This way, if none of the aims are addressed, the VR will not be useful. In the field of engineering education, the most common resources recently designed are based on 3D Virtual Laboratories (3D-VLs) [9,10,12,15,20,[30][31][32][33], since these tools solve several difficulties frequently associated with practical classes in engineering laboratories: (i) the danger of using products or machines; (ii) overcrowded classes; and (iii) timetable schedule availability of the laboratory. Thus, 3D-VLs allow each student to carry out their own practice and obtain an experience very close to the real one.…”
Section: Design Of Vr Applicationsmentioning
confidence: 99%
“…This way, if none of the aims are addressed, the VR will not be useful. In the field of engineering education, the most common resources recently designed are based on 3D Virtual Laboratories (3D-VLs) [9,10,12,15,20,[30][31][32][33], since these tools solve several difficulties frequently associated with practical classes in engineering laboratories: (i) the danger of using products or machines; (ii) overcrowded classes; and (iii) timetable schedule availability of the laboratory. Thus, 3D-VLs allow each student to carry out their own practice and obtain an experience very close to the real one.…”
Section: Design Of Vr Applicationsmentioning
confidence: 99%
“…Lu et al introduced a virtual laboratory to support teaching electron probe Microanalysis. Based on C# and database technology, Xiang and Wang presented a virtual geophysical laboratory system to help users understand the structure of the geophysical equipment and the experimental procedures. VLS based on 2D digital simulation is suitable for many fundamental subjects such as plane stress and mathematical calculation, but not appropriate for applied subjects such as engineering due to the limitation of immersion and interaction.…”
Section: Introductionmentioning
confidence: 99%
“…A virtual laboratory provides multiple users with continuous and simultaneous access to learn an experiment process via a remote server [7,27]. By simulating the experimental process and experimental phenomena on the network, users can experience the experiment operation procedures, understand the experiment data, and observe the results in an immersive and visible virtual environment . In addition, survey has shown that virtual experiments have higher device availability and a higher degree of openness, while the educational value of virtual and on‐site laboratory experiences is comparable based on student performance .…”
Section: Introductionmentioning
confidence: 99%
“…Further, a virtual networking environment permitting students to deploy virtual instances of real‐life network devices has been created at Charles Sturt University . A virtual engine laboratory application for use in automotive engineering education has been proposed to allow the practical teaching of powertrain calibration , and a virtual geophysical laboratory system (VGLS) has been developed to help users understand and master laboratory equipment and experimental procedures in geophysical education . In addition, the CalSev 1.0.2 educational software has been developed to provide teaching support in materials selection seminars , while a virtual electrophysics laboratory has been designed to simulate vacuum systems, powerful pulse technology, accelerator electronic systems, and channels transporting high‐energy particles .…”
Section: Introductionmentioning
confidence: 99%